Offending women: power, punishment and the regulation of desire - Haney, Lynne A. (University of California Press, 2010)
Introduction: an ethnographic journey across states -- Limited government: training women what to need -- Deconstructing dependency: needs, rights, and the struggle for entitlement -- Hybrid states and government from a distance -- State therapeutics: training women what to want -- The empowerment myth: social vulnerability as personal pathology -- The enemies within: fighting the sisters and numbing the self -- Conclusion: states of disentitlement and the therapeutics of neoliberalism